Remote Ischemic Conditioning: From Bench to Bedside - Hausenloy, Derek J.; Lim, Shiang Y. (Frontiers in Physiology, 2012)
Remote ischemic conditioning (RIC) is a therapeutic strategy for protecting organs or tissue against the detrimental effects of acute ischemia-reperfusion injury (IRI). It describes an endogenous phenomenon in which the application of one or more brief cycles of non-lethal ischemia and reperfusion to an organ or tissue protects a remote organ or tissue from a sustained episode of lethal IRI. Although RIC protection was first demonstrated to protect the heart against acute myocardial infarction, its beneficial effects are also seen in other organs (lung, liver, kidney, intestine, brain) and tissues (skeletal muscle) subjected to acute IRI. The recent discovery that RIC can be induced non-invasively by simply inflating and deflating a standard blood pressure cuff placed on the upper arm or leg, has facilitated its translation into the clinical setting, where it has been reported to be beneficial in a variety of cardiac scenarios. In this review article we provide an overview of RIC, the potential underlying mechanisms, and its potential as a novel therapeutic strategy for protecting the heart and other organs from acute IRI.